Effect of Financial Development, Foreign Direct Investment, Globalization, and Urbanization on Energy Consumption: Empirical Evidence From Belt and Road Initiative Partner Countries - Ullah, Atta; Kui, Zhao; Pinglu, Chen; Sheraz, Muhammad (Frontiers in Environmental Science, 2022)
This research aimed to determine the dynamic endogeneity nexus among energy consumption (EC), financial development (FD), foreign direct investment (FDI), globalization (GI), and urbanization (URBAN). The study used 64 countries’ annual panel data on ‘the Belt and Road Initiative (BRI)’ from 2009 to 2019. Moreover, it employed a two-step system GMM, robust and results, that indicates financial development and urbanization are positively correlated with energy consumption, suggesting that these two factors raise the energy demand. Contrastingly, globalization negatively impacts energy demand, implying that global connectivity is essential for BRI countries. Foreign direct investment (FDI) has a positive but insignificant connection with energy consumption. Additionally, the Granger causality test was employed to explore the causal association among the variables, and outcomes reveal a bidirectional causal connection between FD and energy consumption. The study also suggests sustainable energy policy implications, which will be helpful to policymakers and governments for ensuring a balanced, sustainable growth.